Evaluating a Greek Educational Game for Teaching Mathematics and Natural Sciences - Skilodimos, Dimitrios; Skiadas, Petros; Tsami, Eleni (International Journal of Advanced Corporate Learning (iJAC), 2026)
This study introduces KIDEDU (Play – Create – Learn), a digital game-based learning platform developed by an interdisciplinary research team at the University of Piraeus. The project is designed to enhance cognitive engagement and conceptual understanding in mathematics and environmental sciences among Greek primary school pupils aged 6 to 12 years. Structured across three differentiated levels (Grades A–B, C–D, E–F), the game integrates principles of guided discovery learning, differentiated instruction, and curriculum-aligned content to support both individual and collaborative problem-solving. Developed through the collaboration of experts in mathematics, natural sciences, computer science, and medicine, the application bridges formal education materials with immersive digital environments. It aims to provide an alternative pedagogical approach that responds to the evolving needs of contemporary learners and classroom diversity. The broader objective of the project is to promote the scalability of such tools across all levels of education and establish game-based learning as a core instructional method within the Greek educational system. A demonstration of the application’s structure and interactive components is provided, highlighting its potential to improve learning outcomes, student motivation, and engagement through technologyenhanced, inquiry-driven learning experiences.